Nilai-Nilai Pendidikan Multikultural Menurut Al-Qur’an Surah Al-Hujurat Ayat 11 Dan 12 Kajian Ilmu Pendidikan Islam - Sulaiman, Husnan; Mutaqin, Firdan (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
Multicultural values in the teachings of the Quran include recognition, respect and acceptance of cultural diversity. The Quran is not only a spiritual guide, but also emphasizes tolerance, justice, and respect for diversity. Therefore, the integration of Quranic values in people's daily lives can strengthen unity, pluralism, and respect for individual rights. For this reason, more in-depth research is needed to analyze the values of multicultural education according to the Qur'an Surah Al-Hujurat verses 11 and 12 using tafsir and associated with the science of Islamic education. The purpose of this research is to describe: 1) Multicultural Education Values According to Al-Qur'an Surah Al-Hujurat Verses 11 and 12 & 2) Relevance of Multicultural Education Values According to Al-Qur'an Surah Al-Hujurat Verse 11 and 12 with the Study of Islamic Education. This research is one type of literature with the method used is descriptive analytical method. Descriptive analytical method is used to analyze the values of multicultural education. The primary data sources of this research are Al-Qur'an Surah Al-Hujurat verses 11 and 12, Tafsir Al-Misbah, Tafsir Al-Azhar, Tafsir Kemenag and Tafsir Al-Munir while secondary data sources are various references that can support this research.The result of this study is that the values of multicultural education according to the Qur'an Surah Al-Hujurat verses 11 and 12 include: peace, humanity, unity, mutual respect, brotherhood and mutual cooperation. The relevance of multicultural education values to the study of Islamic education Both focus on forming individuals who value diversity, respect the rights of others, and have a whole character according to religious teachings and human values, in order to create democratic, humanist, and pluralist individuals in the educational environment.  Keywords: Education Value, Multicultural, Islamic Education Science